Evidence for the in vivo safety of insulated foamy viral vectors - Browning, Diana L. (Gene Ther, 2016)
Retroviral vector mediated stem cell gene therapy is a promising approach for the treatment of hematopoietic disorders. However, genotoxic side effects from integrated vector proviruses are a significant concern for the use of retroviral vectors in the clinic. Insulated foamy viral (FV) vectors are potentially safer retroviral vectors for hematopoietic stem cell gene therapy. We evaluated two newly identified human insulators, A1 and A2 for use in FV vectors. These insulators had moderate insulating capacity and higher titers than previously developed insulated FV vectors. The A1 insulated FV vector was chosen for comparison with the previously described 650cHS4 insulated FV vector in human cord blood CD34(+) repopulating cells in an immunodeficient mouse model. To maximize the effects of the insulators on the safety of FV vectors, FV vectors containing a highly genotoxic spleen focus forming virus (SFFV) promoter was used to elicit differences in genotoxicity. In vivo, the A1 insulated FV vector showed an approximate 50% reduction in clonal dominance compared to either the 650cHS4 insulated or control FV vectors, although the transduction efficiency of the A1 insulated vector was higher. This data suggests that the A1 insulated FV vector is promising for future pre-clinical and clinical studies.